Tactical Features of Use of Special Knowledge in the Investigation of Torture Committed by Members of the National Police of Ukraine - KOVAL, Ihor M.; KOVAL, Mariia M.; FRANTSUZ, Anatoliy Yo.; KOUCHERETS, Daria V.; SHPILIAREVYCH, Viktoriia V. (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019, 2019)
The article deals with the types of forensic examinations in the investigation of torture committed by officers of the National Police of Ukraine. It was stated that the effectiveness of the investigation of torture committed by members of the National Police depends on the use of the achievements of science and technology and the possibilities of forensic examinations. Based on special knowledge we can find out the mechanism of the formation of traces, tools of torture, the possibility of occurrence of a particular event, phenomenon, fact. A number of investigative actions during which assistance of a specialist or an expert is required are investigated. The list of questions concerning the appointment of a forensic medical examination for determining the severity of bodily injuries is given. It has been confirmed that forensic examinations during the investigation of torture help to identify and study traces and other evidence, determine the psychological state of the participants in the criminal process, determine the degree of bodily harm, the cause of the death of the victim, answer a variety of questions by identifying and studying the facts of the crime and those who committed it.